(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
Lymphedema–distichiasis syndrome (LD, OMIM 153400) is hereditary primary lymphedema with autosomal dominant nature of inheritance and variable expression. LD is characterized by late childhood or pubertal onset of lower limb lymphedema and an aberrant second row of eyelashes (distichiasis) arising from the meibomian glands. Among the molecular reasons behind this condition are the mutations in the FOXC2 gene, a forkhead transcription factor, that plays a role in the formation of lymphatic and vascular systems. In this study, we report the first case of LD from Bangladesh with classical lymphedema–distichiasis syndrome with an eight-base-pair deletion in the FOXC2 gene. ClinVar accession code for this deletion is RCV000007679.3. FOXC2 protein is 501 amino acids long. This deletion of 8 bp (ACGCCGCC) causes frameshift of codons after amino acid number 304. The frameshift creates an altered truncated protein with 154 new amino acids after codon 304. We assume that these changes in the protein may affect its function contributing to the disease manifestations. Further research may confirm these assumptions. J. Bangladesh Acad. Sci. 47(2); 205-213: December 2023